ATAK complex (adrenaline, takotsubo, anaphylaxis, and kounis hypersensitivity-associated coronary syndrome) related to latamoxef administration—a case report - Li, Sheng; Ding, Peng; Wang, Chunxia; Long, Kunlan; Gao, Peiyang (Frontiers in Cardiovascular Medicine, 2024)
Background Adrenaline, stress cardiomyopathy, allergic reactions, and Kounis syndrome (Adrenaline, Takotsubo, Anaphylaxis, Kounis Complex, ATAK) constitute a complex clinical syndrome often associated with endogenous or exogenous adrenaline. Due to its rapid onset, severity, and treatment challenges, it warrants significant attention from clinicians. This article reports a case of Type II Kounis syndrome combined with stress cardiomyopathy (ATAK) triggered by a latamoxef-induced allergy. Case report A 67-year-old male patient with an acute exacerbation of chronic obstructive pulmonary disease was admitted to the respiratory department for treatment. The day before discharge, after receiving a latamoxef infusion for 27 min, the patient developed wheezing, dyspnea, chills, profuse sweating, and an elevated body temperature, necessitating transfer to the ICU for monitoring and treatment. The ECG suggested a suspected myocardial infarction, while bedside echocardiography showed a left ventricular ejection fraction of 40%, segmental dysfunction of the left ventricle, and apical rounding. Emergency coronary angiography revealed 50% segmental eccentric stenosis in the mid-segment of the left anterior descending branch and right coronary artery. The final diagnosis was Type II Kounis Syndrome combined with stress cardiomyopathy due to a latamoxef-induced allergy, i.e., ATAK. Despite aggressive treatment, the patient succumbed to severe cardiogenic shock on the third day in the ICU. Conclusion ATAK is a critical condition that progresses rapidly. For patients experiencing severe allergic reactions, monitoring biomarkers such as Troponin and ECG changes is crucial for timely recognition. If a patient is diagnosed with Kounis syndrome, caution should be exercised in using adrenaline to prevent ATAK.